ANALISIS PENGARUH INDEKS EFEKTIVITAS KOMITE AUDIT TERHADAP JANGKA WAKTU PELAPORAN KEUANGAN - Azizah Putri Eryani Pohan; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2019)
This research is aimed to examine the effect of audit committee effectiveness on companies accuracy in reporting their financial and annual reports on non-financial companies that listed on the Indonesia Stock Exchange (Bursa Efek Indonesia) in 2016. In measuring the effectiveness of the audit committee, the author follows the DeZoort index which divides 4 characteristics: composition, authority, resources, and diligence. According to those characteristics, there are several explanations on a few things namely members independence, background education of members, duties, and responsibilities, the size of the audit committee, and audit committee meeting.This research is conducted through the direct analysis method to financial report which is issued by the Indonesia Stock Exchange and existing web companies. The population of this study is the non-financial sector companies that are listed on the Stock Exchange Indonesia in 2016 with a total sample of 399 companies. The sampling technique in this study is used the purposive sampling.The result of this research shows that the effectiveness of the audit committee has had a significant negative impact on the timeliness of financial reporting. In addition, there are also control variables that support reporting punctuality, namely financial conditions, size of company, industry type, and type of auditor. In variables control, only the financial condition and the type of industry particularly construction that has a significant negative impact on the timeliness of financial reporting.